Measurements of 2D distributions of absorbed dose in protontherapy with Gafchromic EBT3 films. (October 2015) - Gambarini, G.; Regazzoni, V.; Artuso, E.; Giove, D.; Mirandola, A.; Ciocca, M.
Abstract: A study of the response of EBT3 films to protons has been carried out with the aim of finding a simple modality to achieve dose images in which the effect of the film sensitivity dependence on radiation LET is amended. Light transmittance images (around 630 nm) were acquired by means of a CCD camera and the difference of optical density was assumed as dosimeter response. The calibration of EBT3 film was performed by means of protons of 173.61 MeV. Some EBT3 films were exposed, in a solid-water phantom, to proton beams of three different energies (89.17 MeV, 110.96 MeV and 130.57 MeV) and the obtained depth-dose profiles were compared with the calculated profiles. From the ratios of calculated and measured Bragg peaks, a trend of the decrease in EBT3 sensitivity with increasing peak depth has been deduced. A method for correcting the data measured with EBT3 films, utilizing the file of irradiation planning data, has been proposed and tested. The results confirm that the method can be advantageously applied for obtaining spatial distribution of the absorbed dose in proton therapy. Highlights: EBT3 films were calibrated with a proton pencil beam of 173.61 MeV. In-phantom depth-dose image in the SOBP region was measured with EBT3. A method to compensate for the EBT3 under-response, utilizing the file of irradiation planning data, was tested. The central depth-dose profile extracted from the image was compared with that calculated by the TPS. The inter-comparison of measured and calculated profiles has proven that satisfactory correction can be achieved with the proposed methods.